Late Carboniferous Tectonostratigraphy in the Avalon Terrane of Southern New Brunswick - Nance, R. (Atlantic Geology, 1986)
Development of the basement-involved, fold-thrust belt in coastal southern New Brunswick is attributed to dextral transpression associated with regional. CarbonlCerous strike-slip displacements. In the vicinity of Saint John, deformation strongly influenced Westphalian sedimentation in the penecontemporaneous Lancaster and Balls Lake Formations and reflects sustained NW-SE shortening that coincides with a major compressive bend in the E-W, Cobequid-Cbedabucto fault system which records significant, right-lateral Pennsylvanian displacement. Purple conglomerates and lithic wackes of the Balls Lake Formation record syntectonic. NW-progradation of an alluvial fan in response to the uplift of a source to the SB and display facies depicting proximal to ndd-fan. mid-fan, and distal settings. Locally interfingering and laterally equivalent, grey lithic arenites of the Westpbalian Lancaster Formation are the product of major, NE- flowing, meandering streams partially influenced by the prograding distal fan. Initial deformation (Dj) produced NW-directed, basement-involved thrusts that structurally invert regional stratigraphy. Associated lower greenschlst facies metamor-phism accompanied development of a widespread, SB-dipping fabric (Sj). variably expressed as a slaty cleavage, protomylonitic solution cleavage and orthomylonitic foliation. The fabric locally bears a strong but variably oriented mineral lineation (L^) and is axial. planar to NW-vergent, isoclinal ndcrofolds and regional overturned structures (Fi) that plunge gently NE and SW. Renewed thrusting (D2) and back-thrusting (D3) produced conjugate fold sets coaxial with Fj that verge both NW (F2) and SB (F3). Associated axial planar crenulation cleavages (S2 and S3) overprint S\ and dip SB and NW respectively. On-strike variations in deformational style and timing, coupled with the presence of steeply dipping, en echelon zones of Intense deformation, suggest the fold-thrust belt is segmented by right-stepping, convergent wrench faults synthetic to the deeply listric, Cobequid-Cbedabucto system. These faults may shallow into thrusts to form positive flower structures, and locally terminate in thrusts associated with anomalous NW-SE trends in D^ and D2. Thrust uplift in response to transpression on locally downward-steepening, en echelon faults subparallel to the Fundy shore Is proposed to account for the source area of the syntectonic Balls Lake fan. Further displacement and telescoping resulted in structural inversion of regional stratigraphy and deposition of the Balls Lake and Lancaster Formations in advance of an overriding allochthon to the south.